Hubungan Indeks Massa Tubuh dan Lemak Tubuh Terhadap Siklus Haid Karateka Wanita Perguruan Karate-Do Tako Kota Padang - Marzeti, Tiwi; Arif Fadli Muchlis; Wilda Wellis; Septri (Jurnal IKEOR, 2024)
Abstract : Abstract: The problem with this research is that the description of body mass index, body fat and menstrual cycle patterns in female karateka at the Karate-Do Tako College in Padang City is not yet known. This study aims to see the relationship between body mass index and body fat on the menstrual cycle. The method used is descriptive correlational using a cross sectional approach. Female karatekas at the Padang City Tako Karate-Do College are in the age range of 9-21 years. The population in the study consisted of 100 female karateka. Meanwhile, the sample used as research subjects was 30 people using the Purposive Sampling technique. Data were collected using body composition instruments, namely the Omron Karada Scan HBF-375 Body Compositional Monitor scale and microstoise. Meanwhile, the menstrual cycle is assessed using a closed questionnaire. For data analysis techniques, Pearson correlation is used. The research results obtained were (1) There was a significant correlation between Body Mass Index (BMI) and the menstrual cycle in a negative direction and a correlation coefficient of 0.667. (2) There was a significant correlation between body fat and the menstrual cycle in a negative direction and a correlation coefficient of 0.445. From the research results obtained, it can be concluded that Body Mass Index (BMI) and body fat have a significant correlation with the menstrual cycle in female karateka at the Karate-Do Tako College in Padang City with a coefficient of determination of 0.445. Keywords: Body Mass Index (BMI), Body Fat Percent, Menstrual Cycle